Green MOF-resin nano composite adsorbent as well as preparation method and application thereof
A chemically bonded MOF-resin nanocomposite adsorbent addresses mechanical weaknesses of powdered MOFs, ensuring stable industrial CO2 capture and regeneration, enhancing mechanical strength and recyclability.
Patent Information
- Application Number
- CN202411476628.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-31
Smart Images

Figure CN119215865A_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of inorganic and organic composite material synthesis, and in particular to a green MOF-resin nanocomposite adsorbent and a preparation method and application thereof. Background technology:
[0002] With the unabated industrialization and urbanization, the sources of CO2 emissions have diversified, including various sectors such as energy production, transportation and industrial processes. Since CO2 emissions intensify the greenhouse effect and have an adverse impact on the climate, controlling CO2 emission levels has become a global focus.
[0003] In order to reduce the concentration of emitted CO2, a variety of carbon capture and storage technologies need to be adopted. In existing studies, solid adsorption materials used for CO2 capture include activated carbon, zeolite molecular sieves, metal organic frameworks (MOFs), resin materials, etc. Among them, MOFs materials have the characteristics of high porosity, adjustable structure, and large specific surface area, while resin materials have the advantages of porous structure, easy modification, good mechanical and thermal stability, and simple regeneration. Both are promising CO2 adsorption materials.
[0004] MOFs are crystalline materials composed of metal ions or clusters coordinated with organic ligands. These unique properties make MOFs very attractive for gas adsorption and separation processes. Among them, MIL-160(Al) is a MOF material formed by the coordination of aluminum ions and the organic ligand 2,5-furandicarboxylic acid (FDCA). Compared with other metals, aluminum metal is considered to be non-toxic and inexpensive. Its organic ligand FDCA is also very attractive. It is obtained by further oxidation of 5-hydroxymethylfurfural produced from renewable biomass. These factors can significantly reduce the raw material cost of MIL-160(Al) materials. Mild synthesis conditions also make the synthesis process simple and easy to achieve, further reducing the overall cost. These characteristics are very beneficial for its industrial production. However, despite the good properties of MOFs materials, their powdered form has significant defects when used as industrial adsorbents. Powdered MOFs are prone to agglomeration and particle attrition during operation, resulting in reduced efficiency and potential system blockage. Therefore, the effective molding of powdered MOFs is essential. The biggest challenge in constructing molded adsorbents is to ensure that they have higher mechanical strength while maintaining adsorption performance close to that of powders, even if the structure does not change significantly after multiple cycles of regeneration.
[0005] The commonly used method for molding MOFs materials is to use a solid binder through extrusion. Common binders include organic binders such as polyvinyl alcohol (PVA), polyvinyl butyral (PVB), sodium carboxymethyl cellulose, and inorganic binders such as clay and silicone gel. Although the addition of binders usually improves the mechanical properties of molded MOF particles, since there is only a physical bonding effect between the binder and the MOFs powder, the failure of the binder after long-term use will cause the powder to fall off. This problem needs to be solved urgently. Summary of the invention:
[0006] The present invention solves the problems existing in the prior art and provides a green MOF-resin nanocomposite adsorbent and a preparation method and application thereof. The present invention adopts low-cost, non-toxic aluminum metal and a green platform compound 2,5-furandicarboxylic acid (FDCA) synthesized from renewable biomass as raw materials to prepare MOFs; a resin matrix is synthesized in situ and firmly combined with MOFs through chemical bonds to obtain a green composite adsorbent; the adsorbent exists in a spherical form, is easy to recycle, and can be used for industrial CO2 adsorption; the composite adsorbent after use can be regenerated under mild conditions and reused repeatedly, thereby reducing the adsorption cost.
[0007] The first object of the present invention is to provide a method for preparing a green MOF-resin nanocomposite adsorbent, comprising the following steps:
[0008] (1) soaking the resin in anhydrous ethanol for pretreatment to obtain a pretreated resin;
[0009] (2) dissolving an aluminum salt in water to form an aluminum salt solution, and immersing the pretreated resin in step (1) in the aluminum salt solution as a first reactant;
[0010] (3) dissolving 2,5-furandicarboxylic acid in a mixed solution of acetic acid and water as a second reactant;
[0011] (4) The first reactant and the second reactant are mixed uniformly, and the mixture is heated to reflux. The obtained product is washed, dried and sieved to obtain the MOF-resin nanocomposite adsorbent.
[0012] The present invention adopts the MOF in-situ growth method, adds aluminum salt and cation exchange resin into the aqueous solution system to obtain a resin material for fixing metal ions, then adds a green organic ligand FDCA solution, mixes evenly and then heats, and washes and dries the product to obtain a composite adsorbent.
[0013] Preferably, the resin in step (1) is a macroporous cation exchange resin, and the mesh size of the macroporous cation exchange resin is 30 to 60 meshes.
[0014] Further preferably, the macroporous cation exchange resin is selected from one or more of the commercial resins D072, D061, D113, D151, D152, D001, D002, D85, D61 and D62.
[0015] The present invention combines MOFs material with resin, and the cation exchange resin can exchange with metal ions in the solution through the acidic groups it carries, such as sulfonic acid group (-SO3H), carboxyl group (-COOH) or phenol group (-C6H4OH), and firmly fix the metal ions by chemical bonds. The metal aluminum ions are connected with the organic ligand FDCA through coordination bonds to form a more stable composite structure. The composite adsorbent synthesized by this method combines the advantages of MOFs powder and resin matrix, and has great application potential in industrial CO2 adsorption.
[0016] The specific steps of the resin pretreatment are: the resin is immersed in anhydrous ethanol for 24 hours, washed with deionized water, and filtered with a filtrate funnel to obtain the pretreated resin.
[0017] Preferably, the mass ratio of anhydrous ethanol to resin in step (1) is (10-20):1.
[0018] Preferably, the aluminum salt in step (2) is selected from one or more of basic aluminum acetate, aluminum chloride hexahydrate, aluminum acetate and sodium metaaluminate.
[0019] Preferably, in step (2), the mass ratio of aluminum salt to water is 1:(15-30), and the mass ratio of pretreatment resin to water is 1:(10-30); the soaking time is 6-18 hours, and the soaking temperature is 25°C-60°C.
[0020] Preferably, the mass ratio of acetic acid to water in the acetic acid-water mixed solution in step (3) is 1:(5-9), the mass ratio of 2,5-furandicarboxylic acid to the aluminum salt in step (2) is 1:(1-1.2), and the mass ratio of 2,5-furandicarboxylic acid to the acetic acid-water mixed solution is 1:(15-30).
[0021] Preferably, the heating reflux temperature in step (4) is 100° C. and the time is 24 to 36 hours.
[0022] The specific steps of washing, drying and sieving the product are as follows: filtering, washing with deionized water, centrifuging, vacuum drying and sieving the product to obtain a 30-60 mesh MOF-resin nanocomposite adsorbent. The vacuum drying temperature is 70°C to 90°C and the time is 8 to 12 hours.
[0023] The second purpose of the present invention is to protect the green MOF-resin nanocomposite adsorbent prepared by the preparation method.
[0024] The nanocomposite adsorbent provided by the present invention comprises a resin and MOF particles; the resin is a macroporous cation exchange resin, and the MOF particles are combined with the resin through metal aluminum ions.
[0025] The present invention also protects the application of the green MOF-resin nanocomposite adsorbent, and the MOF-resin nanocomposite adsorbent is applied to the adsorption of industrial CO2 at normal temperature and pressure.
[0026] Preferably, the MOF-resin nanocomposite adsorbent is activated under vacuum conditions at 80° C. for 8 to 12 hours to completely desorb CO 2 , thereby achieving regeneration of the MOF-resin nanocomposite adsorbent.
[0027] Compared with the prior art, the present invention has the following advantages and innovations:
[0028] 1. The present invention adopts a water bath condensation reflux method to prepare the MOF-resin nanocomposite adsorbent, which has low requirements on synthesis equipment and is simple and easy to operate, and can realize large-scale industrial preparation.
[0029] 2. The synthesis of the MOF skeleton in the present invention uses the green chemical FDCA as a ligand, acetic acid and water as solvents, which is green and environmentally friendly; aluminum metal is selected as a metal ion source, which is cheap and easily available.
[0030] 3. The present invention utilizes the acidic groups of the cation exchange resin to fix the aluminum ions and then coordinates with the ligand to form a MOF structure. The MOF in the obtained composite material is connected to the resin through a chemical bond and is not easy to fall off, which greatly improves its recycling performance.
[0031] 4. The present invention constructs a composite material with a multi-level pore structure by compounding a microporous MOF material with a macroporous resin, thereby combining the performance advantages of the two.
[0032] 5. The composite adsorbent beads prepared by the present invention have a particle size of 30 to 60 meshes and good mechanical properties, which solves the problems of agglomeration and system blockage that exist when powdered MOFs materials are used. Description of the drawings:
[0033] Figure 1 A schematic diagram of the structural formula of the green MOF-resin nanocomposite adsorbent proposed in the present invention;
[0034] Figure 2 This is a comparison chart of the CO2 static adsorption curves of the 1# composite adsorbent (MIL-160(Al)-D072) synthesized in Example 1 and the resin matrix (D072);
[0035] Figure 3This is a comparison chart of CO2 static adsorption curves of the 2# composite adsorbent (MIL-160(Al)-D061) synthesized in Example 2 and the resin matrix (D061);
[0036] Figure 4 This is a comparison chart of CO2 static adsorption curves of the 3# composite adsorbent (MIL-160(Al)-D113) synthesized in Example 3 and the resin matrix (D113);
[0037] Figure 5 This is a comparison chart of the cycle performance of the 1# composite adsorbent (MIL-160(Al)-D072) synthesized in Example 1. Specific implementation method:
[0038] The following examples are provided to further illustrate the present invention, rather than to limit the present invention.
[0039] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the experimental materials and reagents herein are conventional commercial products in the art.
[0040] Example 1
[0041] A method for preparing a green MOF-resin nanocomposite adsorbent comprises the following steps:
[0042] (1) Weigh 1 g of D072 resin and soak it in a 50 mL conical flask containing 10 g of anhydrous ethanol. After standing for 24 h, wash it repeatedly with deionized water and filter it with a xacin funnel to obtain the pretreated resin;
[0043] (2) Weigh 1.1 g of basic aluminum acetate, pour it into a 100 mL conical flask containing 30 g of water, mix it evenly, immerse it in the pretreated resin, and soak it in a 40° C. water bath reactor for 12 h as the first reactant;
[0044] (3) Weigh 5 g of acetic acid and 25 g of water in a 150 mL three-necked flask, mix them evenly, then add 1 g of 2,5-furandicarboxylic acid and mix again as the second reactant;
[0045] (4) The first reactant was poured into a three-necked flask containing the second reactant and mixed evenly, and the mixture was placed in a water bath reactor and heated under reflux for 24 h. The obtained product was filtered, washed with deionized water, centrifuged, and dried in a vacuum drying oven at 80°C for 10 h to obtain a 30-60 mesh 1#MOF-resin nanocomposite adsorbent MIL-160(Al)-D072.
[0046] Example 2
[0047] A method for preparing a green MOF-resin nanocomposite adsorbent comprises the following steps:
[0048] (1) Weigh 1.5 g of D061 resin and soak it in a 100 mL conical flask containing 30 g of anhydrous ethanol. After standing for 24 h, wash it repeatedly with deionized water and filter it with a xacin funnel to obtain the pretreated resin;
[0049] (2) Weigh 1 g of sodium aluminate, pour it into a 50 mL conical flask containing 15 g of water, mix well, immerse it in the pretreated resin, and soak it in a water bath reactor at 25°C for 18 hours as the first reactant;
[0050] (3) Weigh 1.5 g of acetic acid and 13.5 g of water in a 150 mL three-necked flask, mix them evenly, add 1 g of 2,5-furandicarboxylic acid and mix again as the second reactant;
[0051] (4) The first reactant was poured into a three-necked flask containing the second reactant and mixed evenly, and the mixture was placed in a water bath reactor and heated under reflux for 36 h. The obtained product was filtered, washed with deionized water, centrifuged, and dried in a vacuum drying oven at 70°C for 12 h to obtain a 30-60 mesh 2#MOF-resin nanocomposite adsorbent MIL-160(Al)-D061.
[0052] Example 3
[0053] A method for preparing a green MOF-resin nanocomposite adsorbent comprises the following steps:
[0054] (1) Weigh 1 g of D113 resin and soak it in a 50 mL conical flask containing 15 g of anhydrous ethanol. After standing for 24 h, wash it repeatedly with deionized water and filter it through a xacin funnel to obtain the pretreated resin;
[0055] (2) Weigh 1.2 g of aluminum chloride hexahydrate, pour it into a 100 mL conical flask containing 20 g of water, mix it evenly, immerse it in the pretreated resin, and soak it in a water bath reactor at 60° C. for 6 h as the first reactant;
[0056] (3) Weigh 2.5 g of acetic acid and 17.5 g of water in a 150 mL three-necked flask, mix them evenly, then add 1 g of 2,5-furandicarboxylic acid and mix again as the second reactant;
[0057] (4) The first reactant was poured into a three-necked flask containing the second reactant and mixed evenly, and the mixture was placed in a water bath reactor and heated under reflux for 30 h. The obtained product was filtered, washed with deionized water, centrifuged, and dried in a vacuum drying oven at 90°C for 8 h to obtain a 30-60 mesh 3#MOF-resin nanocomposite adsorbent MIL-160(Al)-D113.
[0058] Example 4
[0059] In order to demonstrate the high adsorption capacity of MOF-resin nanocomposite adsorbent for CO2, the CO2 static adsorption curve test was used to examine the CO2 removal effect of the adsorbent. The specific experimental steps are as follows:
[0060] Take 0.2g of MOF-resin nanocomposite adsorbent and place it in a spherical sample tube, put it into a vacuum degassing device, and degas for 8h at 80℃. Then put it into the specific surface area and pore size distribution analyzer for static adsorption and desorption test. The test conditions are normal temperature and pressure (25℃, 0.1MPa). The removal effect of the corresponding resin matrix on CO2 before composite was also tested under the same mass and conditions. The test results are as follows: Figure 2 , 3 As shown in , 4, the data are shown in Table 1. The three composite adsorbents of Examples 1, 2, and 3 all have higher adsorption performance for CO2 than the resin matrix.
[0061] Table 1 Adsorption of CO2 by three composite adsorbents and their resin matrix
[0062]
[0063] Example 5
[0064] In order to demonstrate the recycling ability of MOF-resin nanocomposite adsorbent, a CO2 static adsorption-regeneration cycle test can be conducted. The specific experimental steps are as follows:
[0065] Take 0.2g of 1#MOF-resin nanocomposite adsorbent MIL-160(Al)-D072 and place it in a spherical sample tube, put it into a vacuum degassing device, and degas it at 80℃ for 8h. Then put it into the specific surface area and pore size distribution analyzer for static adsorption test. After the test, put the sample tube into the vacuum degassing device again, degas it at 80℃ for 8h, and repeat the test. Perform 6 cycles and record the relevant results. The results show that after 6 cycles of use, the CO2 adsorption capacity of the composite adsorbent can still maintain 94.94% of the first cycle adsorption capacity.
[0066] Table 21#MIL-160(Al)-D072 composite adsorbent 6-cycle regeneration performance
[0067] Regeneration times 1 2 3 4 5 6 Adsorption capacity (mg / g) 37.18 37.00 36.58 36.02 35.79 35.25 Adsorption capacity retention rate (%) —— 99.65% 98.52% 97.01% 96.39% 94.94%
[0068] Example 6
[0069] The same as Example 1, except that: in step (1), the mass ratio of anhydrous ethanol to resin is 15:1. In step (2), the mass ratio of basic aluminum acetate to water is 1:15, and the mass ratio of pretreated resin to water is 1:10; the soaking time is 18 hours, and the soaking temperature is 25°C. In step (3), the mass ratio of acetic acid to water in the acetic acid-water mixed solution is 1:7, the mass ratio of 2,5-furandicarboxylic acid to basic aluminum acetate is 1:1, and the mass ratio of 2,5-furandicarboxylic acid to acetic acid-water mixed solution is 1:15. In step (4), the temperature of heating reflux is 100°C and the time is 30 hours.
[0070] The adsorption capacity of CO2 by the composite adsorbent is 37.05 mg / g.
[0071] Example 7
[0072] The same as Example 1, except that: in step (1), the mass ratio of anhydrous ethanol to resin is 20:1. In step (2), the mass ratio of basic aluminum acetate to water is 1:20, and the mass ratio of pretreated resin to water is 1:20; the soaking time is 6 hours, and the soaking temperature is 60°C. In step (3), the mass ratio of acetic acid to water in the acetic acid-water mixed solution is 1:9, the mass ratio of 2,5-furandicarboxylic acid to basic aluminum acetate is 1:1.2, and the mass ratio of 2,5-furandicarboxylic acid to acetic acid-water mixed solution is 1:20. In step (4), the temperature of heating reflux is 100°C, and the time is 36 hours.
[0073] The adsorption capacity of CO2 by the composite adsorbent is 36.87 mg / g.
[0074] The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention. It should be pointed out that for technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a green MOF-resin nanocomposite adsorbent, characterized in that: The steps include: (1) soaking the resin in anhydrous ethanol for pretreatment to obtain a pretreated resin; (2) dissolving an aluminum salt in water to form an aluminum salt solution, and immersing the pretreated resin in step (1) in the aluminum salt solution as a first reactant; (3) dissolving 2,5-furandicarboxylic acid in a mixed solution of acetic acid and water as a second reactant; (4) The first reactant and the second reactant are mixed uniformly, and the mixture is heated to reflux. The obtained product is washed, dried and sieved to obtain the MOF-resin nanocomposite adsorbent.
2. The preparation method according to claim 1, characterized in that: The resin in step (1) is a macroporous cation exchange resin, and the mesh number of the macroporous cation exchange resin is 30 to 60 meshes.
3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of anhydrous ethanol to resin in step (1) is (10-20):
1.
4. The preparation method according to claim 1, characterized in that: In step (2), the aluminum salt is selected from one or more of basic aluminum acetate, aluminum chloride hexahydrate, aluminum acetate and sodium metaaluminate.
5. The preparation method according to claim 1 or 4, characterized in that: In step (2), the mass ratio of aluminum salt to water is 1:(15-30), and the mass ratio of pretreated resin to water is 1:(10-30).
6. The preparation method according to claim 1, characterized in that: The mass ratio of acetic acid to water in the acetic acid-water mixed solution described in step (3) is 1:(5-9), the mass ratio of 2,5-furandicarboxylic acid to the aluminum salt in step (2) is 1:(1-1.2), and the mass ratio of 2,5-furandicarboxylic acid to the acetic acid-water mixed solution is 1:(15-30).
7. The preparation method according to claim 1, characterized in that: The heating reflux temperature in step (4) is 100° C. and the time is 24 to 36 hours.
8. The green MOF-resin nanocomposite adsorbent prepared by the preparation method according to claim 1.
9. The use of the green MOF-resin nanocomposite adsorbent according to claim 8, characterized in that: The MOF-resin nanocomposite adsorbent is applied to the adsorption of industrial CO2 at normal temperature and pressure.
10. The use according to claim 9, characterized in that: The MOF-resin nanocomposite adsorbent was activated at 80°C under vacuum conditions for 8 to 12 hours to completely desorb CO2, thereby achieving regeneration of the MOF-resin nanocomposite adsorbent.
Citation Information
Cited By
Preparation method of zeolite-like imidazole framework ZIF-8
CN120248360A
